The Urgency of Fostering and Oversight of the Notary Honorary Council in Samarinda City - Agustin, Ranti Tri; Mahmudah, Siti (Law Development Journal, 2023)
The guidance and supervision contained in the function of the Notary's Honorary Council really helps maintain the integrity of a notary, ideal guidance of course reduces the level of reporting to the authorized parties regarding notaries regarding legal actions carried out, and the supervision process is to require notaries to make improvements and be accountable for their actions. The following research problem is related to the urgency of guidance and supervision by MKN in the city of Samarinda. The research approach used by the author is a normative juridical approach and a bibliographic data collection method. The approach used is a statutory approach, carried out by reviewing all existing laws and regulations related to the legal issues being handled.